Correlation between homocysteine levels and stroke in patients with acute ischemic stroke - Adnan Kirmit; Aysegul Akagunduz Ege; Ali Guctekin; Mustafa Kemal Basarili; Mujgan Ercan Karadag (Medicine Science, 2019)
Ischemic strokes are mostly caused by atherosclerosis, and increased homocysteine levels are considered to play a role in atherosclerosis. The aim of this study was to investigate serum total homocysteine (tHcy) levels in the first 24 h of ischemic stroke patients and to analyze the correlation between tHcy levels and the clinical severity of ischemic stroke. The study included a total of 151 participants including a patient group of 83 patients diagnosed with acute ischemic stroke and a control group of 68 age- and gender-matched subjects with no history of ischemic vascular diseases between June 2006 and December 2007. Demographic characteristics of were recorded for each participant and stroke severity was assessed using the modified Rankin Scale (mRS) in each patient. Serum tHcy, vitamin B12, folic acid, and fibrinogen levels as well as platelet count and lipid profiles were measured for each participant. Serum tHcy levels were significantly higher and the folic acid levels were significantly lower in the patient group compared to the control group (p [Med-Science 2019; 8(1.000): 11-5]